Opioid Prescribing Patterns of Optometrists in the Medicare Part D Database. Issue 1 (24th January 2022) - Dryden, Stephen C.; O'Malley, Holly A.; Adams, Lindsey R.; Nix, Garrett C.; Rho, Jonathan E.; Vacheron, Albert B.; Fleming, James C.; Fowler, Brian T.
Abstract : SIGNIFICANCE: This study aimed to determine the prescription rates and prescribing trends of opioids by optometrists in the Centers for Medicare & Medicaid Services (CMS) part D database from 2013 to 2017 and to assess opioid prescribing patterns of U.S. optometrists in the CMS part D database. METHODS: With internal review board approval, a retrospective observational cohort study was conducted on optometrists listed in the CMS part D database who prescribed opioids from 2013 to 2017. RESULTS: There was an average of 26, 477 optometrists in the CMS database from 2013 to 2017, of which 5.9% prescribed opioids. Of those prescribing opioids, optometrists wrote an average of 5.9 opioid prescriptions per year. Those writing greater than 10 opioid prescriptions averaged 24.2 annually. Overall, of opioid prescribing optometrists, opioid prescriptions comprised 7% of prescriptions written per year. CONCLUSIONS: Most optometrists do not prescribe opioids, and the vast majority of those who do write few opioid prescriptions. The total number of optometrists prescribing opioids and the total number of opioid prescriptions declined from 2013 to 2017. Further investigation into the opioid prescribing practices by optometrists will help better understand specific pain needs, as opioid prescribing patterns may differ depending on patient population.